Zygophylax levinseni - Gil, Marta; Ramil, Fran; Agís, José Ansín (Zenodo, 2020)
Zygophylax levinseni (Saemundsson, 1911) Zygophylax levinseni : Ramil & Vervoort, 1992: 78–82, figs. 18a–d, 19a–f; Calder & Vervoort, 1998: 35–37, fig. 17a–c; Schuchert, 2001: 71–72; Vervoort, 2006: 240–242, fig. 16. Material examined. MAURIT-1011, stn MUDR20, 16º08´11”N, 16º56´08”W, 405 m, 7-XII-2010: one fragment, without coppiniae. Biology. This species was collected from bottoms of L. pertusa and M. oculata (Altuna Prados & Álvarez Claudio 1994) and was found growing on a sponge, Acryptolaria longitheca (Allman, 1877) (Calder & Vervoort 1998) and a gorgonian axis (Vervoort 2006). Coppiniae have been found only in December (Ramil & Vervoort 1992). Distribution. Zygophylax levinseni has a Northeast Atlantic distribution, from South of Iceland to south of Cape Verde Islands, including the Mid-Atlantic Ridge (Schuchert 2001; Vervoort 2006). The records of the species were summarised by Vervoort (2006). In West Africa, it was collected from Morocco (Ramil & Vervoort 1992), Mauritania (Gil & Ramil 2017a) and Cape Verde Islands (Vervoort 2006). Its bathymetric distribution is between 183 (Altuna Prados & Álvarez Claudio 1994) and 3647 m (Ramil & Vervoort 1992). Our material was obtained from a depth of 405 m. Remarks. Although our colony is only a fragment, it is consistent with the material described by Ramil & Vervoort (1992). : Published as part of Gil, Marta, Ramil, Fran & Agís, José Ansín, 2020, Hydroids (Cnidaria, Hydrozoa) from Mauritanian Coral Mounds, pp. 412-466 in Zootaxa 4878 (3) on page 426, DOI: 10.11646/zootaxa.4878.3.2, http://zenodo.org/record/4425132 : {"references": ["Saemundsson, B. (1911) Bidrag til Kundskaben om de islandske Hydroider. II. Videnskabelige Meddelelser fra Den Danske Naturhistoriske Forening, 63, 67 - 107.", "Ramil, F. & Vervoort, W. (1992) Report on the Hydroida collected by the \" BALGIM \" expedition in and around the Strait of Gibraltar. Zoologische Verhandelingen, Leiden, 277, 1 - 262.", "Calder, D. R. & Vervoort, W. (1998) Some hydroids (Cnidaria: Hydrozoa) from the Mid-Atlantic Ridge, in the North Atlantic Ocean. Zoologische verhandelingen, Leiden, 319, 1 - 65.", "Schuchert, P. (2001) Hydroids of Greenland and Iceland (Cnidaria, Hydrozoa). Bioscience, 53, 1 - 185.", "Vervoort, W. (2006) Leptolida (Cnidaria: Hydrozoa) collected during the CANCAP and Mauritania-II expeditions of the National Hystory, Leiden, the Netherlands [Anthoathecata, various families of Leptothecata and addenda]. Zoologische Mededelingen, Leiden, 80, 181 - 318.", "Altuna Prados, A. & Alvarez Claudio, C. (1994) El genero Zygophylax Quelch, 1885 (Cnidaria, Hydrozoa) en el Golfo de Vizcaya. Miscel. lania Zoologica, 17, 1 - 16.", "Allman, G. J. (1877) Report on the Hydroida collected during the exploration of the Gulf Stream by L. F. de Pourtales, assistant United States Coast Survey. Memoirs of the Museum of Comparative Zoology at Harvard College, 5 (2), 1 - 66. https: // doi. org / 10.5962 / bhl. title. 15852", "Gil, M. & Ramil, F. (2017 a) Hydrozoans from Mauritanian Deep-Waters. In: Ramos, A., Ramil, F. & Sanz, J. L. (Eds.), Deep sea ecosystems off Mauritania: Researching marine biodiversity and habitats in West African Deep-waters. Springer, Dordrecht, pp. 419 - 444. https: // doi. org / 10.1007 / 978 - 94 - 024 - 1023 - 5 _ 11"]}